Breastfeeding Monitoring Improves Maternal Self-Efficacy and Satisfaction. Issue 6 (November 2020) - Ahmed, Azza H.; Roumani, Ali M.
Abstract: Purpose: The purpose of this study was to determine the effects of an interactive web-based breastfeeding monitoring system on breastfeeding self-efficacy and satisfaction among mothers of full-term infants at 1, 2, and 3 months after hospital discharge. Study Design: We conducted a secondary data analysis of our two-arm, repeated-measures randomized controlled trial that took place in three Midwestern hospitals. Participants were assigned to either control or intervention groups using random numbers. Of the 141 mother–baby dyads enrolled and randomized, 35 dropped out of the study, leaving 57 mothers in the control group and 49 in the intervention group. Mothers in both groups received care based on the hospital protocol, but mothers in the intervention group were also given access to an interactive web-based breastfeeding monitoring system prior to discharge. Participants were asked to enter breastfeeding data, receive educational messages for 30 days, and complete the Breastfeeding Self-Efficacy Scale (BFSE) at 1, 2, and 3 months and the Maternal Breastfeeding Evaluation Scale (MBFES) at 3 months. Mothers received feedback in case of breastfeeding problems. Results: A significant difference between groups in BFSE at the 2 and 3 months ( p = 0.04; p = 0.04) with medium effect size (0.52, 0.53) was found. There was a significant difference between groups in the total score of MBFES ( p = 0.02, effect size 0.53). Mean scores were 122.2, SD = 17.68 for intervention and 112.8, SD = 18.03 for control group. The MBFES scores were positively correlated to BFSE scores among intervention group at all time points ( r = .714, n = 45, p < .00; r = .611, n = 41, p < .00; r = .637, n = 39, p < .00). Clinical Implications: Interactive web-based breastfeeding monitoring improved maternal breastfeeding self-efficacy and satisfaction and may be a promising innovation to promote maternal breastfeeding self-efficacy and satisfaction. Abstract : Breastfeeding apps available on smart phones may be a helpful tool for new mothers to achieve their breastfeeding goals. In this study, mothers used the breastfeeding app for 3 months postpartum while breastfeeding. When compared to mothers who did not use the app, those that did had higher scores on maternal self-efficacy and satisfaction with breastfeeding.